Precise measurement of the top quark mass in dilepton decays using optimized neutrino weighting - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Elsevier, 2016)
We measure the top quark mass in dilepton final states of tt events in pp collisions at √s = 1.96 TeV, using data corresponding to an integrated luminosity of 9.7 fb-1 at the Fermilab Tevatron Collider. The analysis features a comprehensive optimization of the neutrino weighting method to minimize the statistical uncertainties. We also improve the calibration of jet energies using the calibration determined in tt → lepton + jets events, which reduces the otherwise limiting systematic uncertainty from the jet energy scale. The measured top quark mass is mt=173.32±1.36(stat)±0.85(syst) GeV.